Child-Friendliness of Urban Space in the Example of Łabędy - Szewiola Helena (Architecture, Civil Engineering, Environment, 2023)
Children have long been a group whose needs and perspectives have been widely ignored in public spaces, despite several international legal documents and regulations proving their rights in the city. Based on those, child-friendliness criteria have been proposed and described. The established guidelines of: mobility and access, safety and security, attractiveness and comfort have been further explored through surveys conducted with minors. Subsequently, these criteria have been applied to the chosen district of Łabędy, to examine how they present in existing public spaces.